Bicameralism in the European Union: parliamentary scrutiny as a tool for reinforcing party unity. Issue 2 (4th March 2017) - Finke, Daniel
Abstract: During recent years, the European Union has increasingly been portrayed as a bicameral political system in which political parties build bridges across the European Parliament (EP) and the Council. From this perspective, national parties' representation in the Council should affect their members' voting behaviour in the EP. Survey evidence reveals that most members of the EP (MEPs) frequently receive voting instructions from 'their' ministers. Accordingly, these MEPs should have a higher likelihood of defecting from their European Political Group. The observed voting instructions imply that the voting preferences of MEPs and their ministers differ. This article argues that parliamentary scrutiny may be one way effectively to coordinate on a common position at an early stage and, consequently, reinforce party unity at the voting stage. However, effective scrutiny depends on national parliaments being strong enough. On the empirical side, this article studies the voting behaviour of MEPs from eight member states during the Sixth EP. We include four national parliaments which the literature conceives of as being strong (DK, DE, SF, SK) and four parliaments conceived of as being weak (FR, IE, IT, UK). Overall, the results support the theoretical argument, thereby demonstrating how domestic-level scrutiny affects EU-level voting behaviour.